A student's plea to professor North: An episode in academic politics and interdisciplinarity in the Reagan years - Rafael Galv\~ao de Almeida (Duke University, Center for the History of Political Economy (CHOPE), 2021)
This paper introduces and reproduces a letter written to Douglass North asking for support against the closing of the sociology department at Washington University in St. Louis.
Keywords: 330; Douglass North; Melissa Tarr; Martin Israel; David M. Rubenstein Rare Book & Manuscript Library; Duke University